A 'telephone first' approach to demand management in English general practice: a multimethod evaluation - Jennifer Newbould; Sarah Ball; Gary Abel; Matthew Barclay; Tray Brown; Jennie Corbett; Brett Doble; Marc Elliott; Josephine Exley; Anna Knack; Adam Martin; Emma Pitchforth; et al. (National Institute for Health Research, 2019)
Background: The increasing difficulty experienced by general practices in meeting patient demand is leading to new approaches being tried, including greater use of telephone consulting. Objectives: To evaluate a 'telephone first' approach, in which all patients requesting a general practitioner (GP) appointment are asked to speak to a GP on the telephone first. Methods: The study used a controlled before-and-after (time-series) approach using national reference data sets; it also incorporated economic and qualitative elements. There was a comparison between 146 practices using the 'telephone first' approach and control practices in England with regard to GP Patient Survey scores and secondary care utilisation (Hospital Episode Statistics). A practice manager survey was used in the 'telephone first' practices. There was an analysis of practice data and the patient surveys conducted in 20 practices using the 'telephone first' approach. Interviews were conducted with 43 patients and 49 primary care staff. The study also included an analysis of costs. Results: Following the introduction of the 'telephone first' approach, the average number of face-to-face consultations in practices decreased by 38% [95% confidence interval (CI) 29% to 45%; p < 0.0001], whereas there was a 12-fold increase in telephone consultations (95% CI 6.3-fold to 22.9-fold; p < 0.0001). The average durations of consultations decreased, which, when combined with the increased number of consultations, we estimate led to an overall increase of 8% in the mean time spent consulting by GPs, although there was a large amount of uncertainty (95% CI -1% to 17%; p = 0.0883). These average workload figures mask wide variation between practices, with some practices experiencing a substantial reduction in workload. Comparing 'telephone first' practices with control practices in England in terms of scores in the national GP Patient Survey, there was an improvement of 20 percentage points in responses to the survey question on length of time to get to see or speak to a doctor or nurse. Other responses were slightly negative. The introduction of the 'telephone first' approach was followed by a small (2%) increase in hospital admissions; there was no initial change in accident and emergency (A&E) department attendance, but there was a subsequent small (2%) decrease in the rate of increase in A&E attendances. We found no evidence that the 'telephone first' approach would produce net reductions in secondary care costs. Patients and staff expressed a wide range of both positive and negative views in interviews. Conclusions: The 'telephone first' approach shows that many problems in general practice can be dealt with on the telephone. However, the approach does not suit all patients and is not a panacea for meeting demand for care, and it is unlikely to reduce secondary care costs. Future research could include identifying how telephone consulting best meets the needs of different patient groups and practices in varying circumstances and how resources can be tailored to predictable patterns of demand. Limitations: We acknowledge a number of limitations to our approach. We did not conduct a systematic review of the literature, data collected from clinical administrative records were not originally designed for research purposes and for one element of the study we had no control data. In the economic analysis, we relied on practice managers' perceptions of staff changes attributed to the 'telephone first' approach. In our qualitative work and patient survey, we have some evidence that the practices that participated in that element of the study had a more positive patient experience than those that did not. Funding: The National Institute for Health Research Health Services and Delivery Research programme.